1993
DOI: 10.1128/jvi.67.5.2844-2852.1993
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1-specific cytotoxic T lymphocytes release gamma interferon, tumor necrosis factor alpha (TNF-alpha), and TNF-beta when they encounter their target antigens

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection is associated with elevated levels of inflammatory cytokines in the serum and cerebrospinal fluid of infected persons, but the sources of these proteins as well as the specific stimuli which trigger their production and release have not been fully defined. In this study, we evaluated the ability of HIV-1-specific cytotoxic T-lymphocyte (CTL) clones derived from seropositive persons to release gamma interferon (IFN-y), tumor necrosis factor alpha (TNF-a), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
4

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(34 citation statements)
references
References 59 publications
3
27
0
4
Order By: Relevance
“…Double-labeling experiments combining and in situ hybridization showed that the vast majority of IFN-y gene-expressing cells in lymph nodes from HIVinfected patients were not CD4" T-he!per lymphocytes but rather CD8'' T cells (Emilie et al 1990). This observation in lymphoid organs is in agreement with more recent data showing that HIV-specific CDS"" cytotoxic T-lymphocyte (CTL) clones obtained from cerebrospinal fluid from HIV-infected patients produce IFN-7 when challenged with HIV antigen-presenting cells (Jassoy et al 1993). It is also in keeping with the finding that HlV-specific CTL are present in lymphoid organs from HIV-infected patients (Hadida et a!.…”
Section: Production Of Thl-type Lymphokines In Lymphoid Organs Of Hivsupporting
confidence: 91%
“…Double-labeling experiments combining and in situ hybridization showed that the vast majority of IFN-y gene-expressing cells in lymph nodes from HIVinfected patients were not CD4" T-he!per lymphocytes but rather CD8'' T cells (Emilie et al 1990). This observation in lymphoid organs is in agreement with more recent data showing that HIV-specific CDS"" cytotoxic T-lymphocyte (CTL) clones obtained from cerebrospinal fluid from HIV-infected patients produce IFN-7 when challenged with HIV antigen-presenting cells (Jassoy et al 1993). It is also in keeping with the finding that HlV-specific CTL are present in lymphoid organs from HIV-infected patients (Hadida et a!.…”
Section: Production Of Thl-type Lymphokines In Lymphoid Organs Of Hivsupporting
confidence: 91%
“…In conclusion, we have found no evidence of a defect in IL-2 or TNFin CVID, unlike IFN-. The increase in numbers of cells able to make IFNin CVID would be compatible with a chronic viral infection, as has been described with HIV [27]. However, since no one virus has been implicated in CVID, it is possible that a # 1996 Blackwell Science Ltd, Clinical and Experimental Immunology, 105:517-522 Fig.…”
Section: Discussionmentioning
confidence: 85%
“…However, an association between a type 1 immune response to HIV-1 antigens and a restricted virus expression has been suggested by Clerici et al, who recently obtained a dominant type 1 cytokine profile together with a reduced prevalence of HIV-1 isolation in vitro [2]. RANTES and other chemokines, in addition to cytokines like IFN-g, may control HIV-1 directly or indirectly through the attraction and activation of effector cells [4,19,20]. Our study of the relationship between production of RANTES in HIV-1 p24-activated whole blood cultures and the plasma viral load support the hypothesis of the important role of an immune response of gag-specific T cells to restrict virus expression.…”
Section: Discussionmentioning
confidence: 99%